EFEKTIVITAS MEDIA AUDIO VISUAL TERHADAP PENINGKATAN PENGETAHUAN MAHASISWA TENTANG KONSEP TERMOREGULASI - Jamariah, Siti; Amir, Yufitriana; Utami, Sri (Poltekkes Kemenkes Malang, 2022)
The Covid 19 pandemic has caused major changes in all aspects of life, one of which is education. Audio visual media are learning media needed during the Covid 19 pandemic. The human senses have different percentage levels in receiving information. The sense of sight and the sense of hearing have a percentage of 50 Percent in receiving information. This study aims to determine the effectiveness of audio visual media to increase students knowledge about the concept of thermoregulation. The research method used is quasy experiment with pretest posttest design with control group. The research sample amounted to 34 people who were divided into 17 experimental groups who were given audio visual and powerpoint and 17 control groups who were given powerpoints taken based on inclusion criteria with random sampling technique. This research instrument uses a questionnaire that has been tested for validity and reliability. The analysis used is univariate and bivariate analysis using the Dependent T Test and Mann Whitney. The results of this study indicate that the average level of knowledge in the experimental group was 82.06 and in the control group was 68.53 with P Value of 0.004 Less than a 0.05. Statistically there is an effect of effective audio visual media on increasing student knowledge about the concept of thermoregulation.